The Effects of Periodicity, Height and Depth of Freshening on the Resin Yield from Young Pinus roxburghii Sargent and Seasonal Response - Rajkhowa, S.; Khan, M. A. Waheed (Indian Forester, 1962)
A substantial increase in the annual yield of resin from young Pinus roxburghii can be obtained by using short tapping cycles. The response to shorter cycles is very little in the first month of tapping, but increases rapidly as the summer advances. Again, by August, the response drops off suddenly. This suggests a varying frequency of tapping at different months of the year. A tentative scheme of tapping suggested has the advantage that tapping is done only during four months of the year, giving the tree rest for 8 months in each year, and yet producing nearly double the yield obtained under the conventional method. With short tapping cycles, it is also possible to reorganise the field work so that the tapping cost does not increase.